When Love Ails: Lovesickness and the Authenticity of Emotions in Plautus’ Cistellaria - Todorović, Jelena (Acta historiae medicinae, stomatologiae, pharmaciae, medicinae veterinariae, 2025)
This paper examines the first extant instance of the medicalization of love in Roman literature. In Plautus’ Cistellaria, love is not just conceived through a conventional comic lens of erotic desire but as a psychosomatic disorder, expressed through symptoms that blur the boundary between mental disturbance and bodily illness. The analysis shows how Plautus integrates medical and popular knowledge to construct a model of amor that ancient audiences could recognize as pathological. This medicalization of passion serves a distinctly literary purpose: by grounding emotion in physical and cognitive symptoms, Plautus grants psychological depth and credibility to his protagonists. The authority of medical thought thus legitimizes what comedy typically trivializes, sincere feeling and genuine distress. Cistellaria emerges as a case study in how Roman literature appropriated scientific discourse to substantiate and shape narrative coherence. The study situates this medicalization of passion within broader ancient discourses on disease and affects, revealing how Plautus’ comedy participates in the cultural translation of medical knowledge.